2016
DOI: 10.1002/2016jb012970
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of inelastic strain during creep of Carrara marble: Microscale strain measurement technique

Abstract: We combined the split cylinder technique with microfabrication technology to observe strain heterogeneities that were produced during high‐pressure transient creep of Carrara marble. Samples were patterned with a custom‐designed grid of markers spaced 10 µm apart and containing an embedded coordinate system. The microscale strain measurement (MSSM) technique described here allowed us to analyze the local strain distribution with unprecedented detail over large regions. The description of the strain field is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 107 publications
0
25
0
Order By: Relevance
“…[] are difficult to interpret with simplistic classical models, requiring us to explore new methods, particularly those allowing us to detect a single‐grain to multiple‐grain‐scale deformation directly. In this study, we will show that observations of sample surfaces with etched fine‐scale markers are a powerful tool allowing us to detect microdeformation processes [ Quintanilla‐Terminel and Evans , ], especially GBS and grain rotation, which we consider key processes for CPO development during diffusion creep [ Miyazaki et al ., ]. Together with the mechanical data, we are able to interpret the mechanisms involved, which is essentially impossible using conventional experimental techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[] are difficult to interpret with simplistic classical models, requiring us to explore new methods, particularly those allowing us to detect a single‐grain to multiple‐grain‐scale deformation directly. In this study, we will show that observations of sample surfaces with etched fine‐scale markers are a powerful tool allowing us to detect microdeformation processes [ Quintanilla‐Terminel and Evans , ], especially GBS and grain rotation, which we consider key processes for CPO development during diffusion creep [ Miyazaki et al ., ]. Together with the mechanical data, we are able to interpret the mechanisms involved, which is essentially impossible using conventional experimental techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Different image processing techniques can be used for locating the markers before and after deformation, such as a convolution (Biery et al, 2003) or a Hough transform algorithm (Quintanilla-Terminel and Evans, 2016). Depending on the application, the user could rely on the regularity of the grid and not identify the markers before deformation.…”
Section: Marker Locationmentioning
confidence: 99%
“…(a) The n-point configurations for n = 3, 5, 9, and 25. (b) Corresponding strain maps and strain distributions for strain along axis 1 in the sample reference (see insert for reference frame) for a Carrara marble cylinder isostatically annealed at T = 700 • C and P c = 300 MPa for 3 h. (c) Corresponding strain distribution for each strain map; it can be observed that the mean is always 0 but the spread of the distribution becomes smaller with increasing n. Modified after Quintanilla-Terminel and Evans (2016). ence between the modeled and the measured material lines, dx * i = F • dX and dx i , respectively.…”
Section: The N-point Analysismentioning
confidence: 99%
See 2 more Smart Citations